Stability, efficiency and financial risks of islamic banks in conditions of instability of global financial system - Tatyana Mazurina; Shukrullokhon Sharipov (Управление)
In modern conditions of implementation Islamic model of banking, the issues of increasing efficiency of its activities and ensuring the long-term stability of Islamic banks come to the fore. Article analyzes the activities of Islamic banks in the post-crisis period, both in the global Islamic banking sector as a whole, and in the context of individual countries in which Islamic banks are predominantly or significantly represented, as well as financial risks that pose a threat of losses for Islamic banks. It has been concluded that the Islamic financial system is becoming one of the most important components of the international financial system, and Islamic banks within the global financial system are becoming more recognized and competitive, as they demonstrate a sufficiently high efficiency and stability of activity, a positive trend of development. Analysis found that Islamic banking has demonstrated its reliability and stability in the post-crisis period and continues to be a viable and effective mechanism of financial intermediation in the conditions of global financial system instability. The differences in the functioning and performance of Islamic banks in different countries within a single consolidated Islamic banking system have been revealed, a comparative analysis effectiveness of banking sectors a number of Muslim countries has been given, the directions of development of Islamic banking in them have been shown. Conclusions have been drawn on the need for Islamic banks to introduce effective mechanisms for monitoring and managing financial and investment risks in order to increase their ability to withstand adverse external factors, since in the future, despite the positive trends in the activities of Islamic banks, there are potential financial risks due to the growth of their current costs associated with the possibility of potential deterioration in the quality of assets and reduction in the level of profit.